2005
DOI: 10.1007/s00421-005-0105-5
|View full text |Cite
|
Sign up to set email alerts
|

The physiological response of ankle systolic blood pressure and ankle to brachial index after maximal exercise in athletes is dependent on age

Abstract: The development of sports activities in the over forties has increased the number of middle-aged patients performing heavy-load exercise. The normal response of ankle systolic blood pressure (ASBP) and ankle to brachial index (ABI) to intense exercise is known in young athletes, but little is known for other age groups. Three groups of 21 athletes: <20 (G1), 20-40 (G2), and >40 (G3) years old, respectively, were studied. ASBP and brachial systolic blood pressure (BSBP) were measured simultaneously before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
1
5
0
1
Order By: Relevance
“…This was not the case for our population. Our results are consistent with previous studies that have demonstrated an increase in the resting ABI value with age in apparently healthy subjects and with the preliminary monocentric post‐exercise results observed in a small group of athletes . There are various explanations for this observation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was not the case for our population. Our results are consistent with previous studies that have demonstrated an increase in the resting ABI value with age in apparently healthy subjects and with the preliminary monocentric post‐exercise results observed in a small group of athletes . There are various explanations for this observation.…”
Section: Discussionsupporting
confidence: 93%
“…While results after both types of exercise correlate fairly well, the slope of the relationship is not one suggesting that the response for the two type of tests is not identical . Third, the changes in ASBP or ABI are highly dependent on the intensity level of exercise as well as the delay from end exercise . Forth, age effect on vasodilator capacity in the area of vasodilation of the active muscles might be resulting in lower acceptable ankle to arm difference (ABI) in young than in healthy subjects …”
Section: Discussionmentioning
confidence: 99%
“… 19 Furthermore, ageing induces changes in the arterial wall 20 and this can modify the pressure and the ABI. 21 Ideally, healthy control subjects should be age matched. Moreover, the 1-minute duration of exercise used by Laing et al is markedly different than current protocols in most laboratories, and extrapolation to a 5-minute walk is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showing post-exercise ABI decreased not only in normal subjects but also in patients with PAOD [24][25][26][27]. Generally, HR increased in response to the extent of exercise.…”
Section: Discussionmentioning
confidence: 98%